2019
DOI: 10.1002/jcb.28774
|View full text |Cite
|
Sign up to set email alerts
|

Hesperidin‐CAMKIV interaction and its impact on cell proliferation and apoptosis in the human hepatic carcinoma and neuroblastoma cells

Abstract: Calcium/calmodulin‐dependent protein kinase IV (CAMKIV) is a key regulatory molecule of cell signaling, and thereby controls its growth and proliferation, including expression of certain genes. The overexpression of CAMKIV is directly associated with the development of different types of cancers. Hesperidin is abundantly found in citrus fruits and exhibits wide range of pharmacological activities including anti‐inflammatory, antibacterial and anticancerous effects. We have investigated binding mechanism of hes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…CaMKIV possess an inherent ATPase activity [ 67 , 68 ]. Thus, we have employed BIOMOL reagent-based kinase assay wherein the inorganic phosphate released by the hydrolysis of ATP in a reaction catalyzed by CaMKIV forms a green-colored complex with malachite green.…”
Section: Resultsmentioning
confidence: 99%
“…CaMKIV possess an inherent ATPase activity [ 67 , 68 ]. Thus, we have employed BIOMOL reagent-based kinase assay wherein the inorganic phosphate released by the hydrolysis of ATP in a reaction catalyzed by CaMKIV forms a green-colored complex with malachite green.…”
Section: Resultsmentioning
confidence: 99%
“…HDN also attenuated cerebral I/R injury through inhibiting the apoptotic pathway (47). However, studies have also reported that HDN induces apoptosis to reduce cancer cell prolif-eration (15,48). These differences may be due to the acute nature of I/R injury compared with the chronic induction of carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…A recent 25 evidence showed that Hesp is a potent inhibitor of calcium/calmodulin-dependent protein kinase IV (CAMKIV), and by inhibiting CAMKIV along with activating the caspase-3-dependent intrinsic pathway through the upregulation of pro-apoptotic protein, Bax (BCL2 associated X, apoptosis regulator), Hesp exerts its anti-apoptotic and anticancer activities. 27…”
Section: Hesperidin: Molecular Mechanisms Of Actionmentioning
confidence: 99%